Isaac N. Phillips, The Revised Ordinances of the City of Bloomington, A.D. 1876: Comprising the general ordinances, acts of incorporation, and other laws affecting the City of Bloomington (Bloomington, IL: Leader Steam Printing and Publishing House, 1876), 58. Division 3, Offenses Against Public Safety, Convenience and Health, §1, Firing Cannon, Guns, Fire-Crackers, etc. - (:unkn) unknown (General Publisher, 1876)
Prohibited firing or dischargng any cannon, gun, pistol, revolver, or any firearm of any description, or explode any squib, fire-cracker, torpedo, or other thing containing powder or other explosive material. Violators fined not less than two nor more than twenty dollars.
--
Keywords: DISCHARGE